2021
DOI: 10.1021/acs.iecr.1c00108
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like Pt/Fe2O3–CeO2 Catalysts for Highly Efficient Low-Temperature Catalytic Oxidation of Toluene

Abstract: A series of porous Pt/Fe x Ce y microflowers have been synthesized through a solvothermal method. The well-defined mesoporous structure promotes gas distribution as well as even dispersion of active species, thus exposing more active sites and improving the catalytic efficiency for low-temperature toluene removal. The catalyst composition can be regulated by changing the Fe/Ce molar ratio and Pt loading content. Among the samples, 1 wt % Pt/Fe3Ce1 performed the best, with a reaction temperature for 90% toluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The XRD of these samples reveals that the α-Fe 2 O 3 structure of the catalysts is not changed by the low concentration of doped Ce, but the peak in Ce-doped samples gradually broadened compared to that of pure Fe 2 O 3 -350 °C. The slight decrease in the iron content and the sintering inhibition of dopant cerium resulted in poor crystallinity. , The structure and composition of the as-prepared catalysts were analyzed by Raman spectroscopy (Figure S1). The sharp peak at 460 cm –1 attributed to the F 2g vibration mode of a fluorite-type structure could only be observed in CeO 2 -350 °C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD of these samples reveals that the α-Fe 2 O 3 structure of the catalysts is not changed by the low concentration of doped Ce, but the peak in Ce-doped samples gradually broadened compared to that of pure Fe 2 O 3 -350 °C. The slight decrease in the iron content and the sintering inhibition of dopant cerium resulted in poor crystallinity. , The structure and composition of the as-prepared catalysts were analyzed by Raman spectroscopy (Figure S1). The sharp peak at 460 cm –1 attributed to the F 2g vibration mode of a fluorite-type structure could only be observed in CeO 2 -350 °C .…”
Section: Resultsmentioning
confidence: 99%
“…The slight decrease in the iron content and the sintering inhibition of dopant cerium resulted in poor crystallinity. 41,42 The structure and composition of the as-prepared catalysts were analyzed by Raman spectroscopy (Figure S1). The sharp peak at 460 cm −1 attributed to the F 2g vibration mode of a fluorite-type structure could only be observed in CeO 2 -350 °C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition, Zhou et al (2021) reported the preparation of Pt nanoparticle-loaded Fe 2 O 3 –CeO 2 catalysts for efficient catalytic oxidation of toluene, showing the superior catalytic activity of this catalyst for toluene oxidation compared with unmodified Fe 2 O 3 –CeO 2 . It was found that the high concentration of active surface lattice oxygen, whose formation is promoted by both the addition of Pt and the synergism between Fe 2 O 3 and CeO 2 , plays a vital role in efficient toluene combustion . These studies demonstrated that active surface lattice oxygen of a catalyst is a key factor for effective VOC combustion.…”
Section: Introductionmentioning
confidence: 97%
“…These studies demonstrated that active surface lattice oxygen of a catalyst is a key factor for effective VOC combustion. Various transitional metal oxides such as Fe 2 O 3 , MnO 2 , Co 3 O 4 , Cr 2 O 3 , and CeO 2 have frequently been utilized as supports for noble metal nanoparticles (Pd, Au, Rh, and Pt) due to their excellent oxygen storage capacity and good redox properties for oxygen activation . Most previous studies have focused on the catalytic combustion of aromatics and heteroatom-containing organic compounds, such as benzene, toluene, o -xylene, and trichloroethylene. In contrast, few studies have focused on the catalytic combustion of cyclohexane due to its chemically inactive molecular structure and stability, resulting in most catalysts being unsuitable for its catalytic decomposition under low-temperature conditions. , In addition, little is known about the interfacial VOC transformation process and oxidation mechanisms associated with noble metals and surface oxygen vacancices in VOC combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the general combustion method, catalytic oxidation is considered a versatile way for completely converting toxic VOCs into CO 2 and H 2 O with hardly any formation of NO x . , Designing highly active catalysts is the key issue for achieving practical applications of this technique. However, supported platinum group metals (PGMs) are still the most efficient catalysts for the catalytic removal of VOCs. Considering their high cost, low thermal stability, and poisoning tendency, their wide application will be limited. Therefore, it is highly desirable to explore alternative catalysts with low cost and high performance for deep oxidation of VOCs.…”
Section: Introductionmentioning
confidence: 99%